2021
DOI: 10.1097/mou.0000000000000969
|View full text |Cite
|
Sign up to set email alerts
|

Best nonsurgical managements of acute urinary retention: what's new?

Abstract: Purpose of reviewTo provide a comprehensive review of the nonsurgical management of acute urinary retention (AUR). Recent findingsA recent meta-analysis confirmed that a-blockers are associated with higher rates of successful trial without catheter (TWOC) compared with placebo, while combination therapies do not significantly reduce the rate of recatheterization. Compared with standard TWOC, bladder perfusion with physiological serum prior to catheter removal is a simple and cost-effective method to increase T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“… 22 Several alpha blockers that have been tested in patients with AUR have been shown to increase the rates of successful TWOC. 23 A recent meta-analysis showed that, compared to placebo, most alpha blockers provided significantly higher rates of successful TWOC, including alfuzosin (OR: 2.28, 95% CI: 1.55–3.36), silodosin (OR: 5.68, 95% CI: 1.84–17.5), and tamsulosin (OR: 2.40, 95% CI: 1.29–4.45), but not doxazosin (OR: 1.22, 95% CI: 0.38–3.93). 20 The duration of providing alpha blocker before TWOC remains under discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Several alpha blockers that have been tested in patients with AUR have been shown to increase the rates of successful TWOC. 23 A recent meta-analysis showed that, compared to placebo, most alpha blockers provided significantly higher rates of successful TWOC, including alfuzosin (OR: 2.28, 95% CI: 1.55–3.36), silodosin (OR: 5.68, 95% CI: 1.84–17.5), and tamsulosin (OR: 2.40, 95% CI: 1.29–4.45), but not doxazosin (OR: 1.22, 95% CI: 0.38–3.93). 20 The duration of providing alpha blocker before TWOC remains under discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increasing the duration of alpha blocker prior to TWOC seems to provide no significant benefit, with the level of evidence about this point remaining low. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Urinary retention secondary to benign prostate hyperplasia (BPH) is a challenging yet not uncommon issue faced among the geriatric population, with more than 10% of men in their 70s estimated to be diagnosed with urinary retention. 1 Once diagnosed, these patients become catheter-dependent, and their quality of life consequently suffers. Additionally, they become at risk for catheter-associated complications such as urinary tract infections (UTI), urethral bleeding, hematuria, urethral stricture, and physical discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary retention secondary to benign prostate hyperplasia (BPH) is a challenging yet not uncommon issue faced among the geriatric population, with more than 10% of men in their 70s estimated to be diagnosed with urinary retention 1 . Once diagnosed, these patients become catheter‐dependent, and their quality of life consequently suffers.…”
Section: Introductionmentioning
confidence: 99%
“…The immediate management of benign prostatic obstruction (BPO)-related acute urinary retention (AUR) involves insertion of an indwelling urethral catheter (IUC) or suprapubic catheter, followed by a trial without catheter (TWOC) [1] . In cases of TWOC failure, urethral recatheterization should be avoided, as it is associated with time-dependent complications and patient discomfort [2] , [3] .…”
mentioning
confidence: 99%